Impulse Control Disorder in Parkinson's Disease: A Meta-Analysis of Cognitive, Affective, and Motivational Correlates - Martini, Alice; Dal Lago, Denise; Edelstyn, Nicola M. J.; Grange, James A.; Tamburin, Stefano (Frontiers in Neurology, 2018)
Background In Parkinson’s disease (PD), impulse control disorders (ICDs) develop as side-effect of dopaminergic replacement therapy (DRT). Cognitive, affective and motivational correlates of ICD in medicated PD patients are debated. Here, we systematically reviewed and meta-analyzed the evidence for an association between ICD in PD and cognitive, affective and motivational abnormalities. Methods A systematic review and meta-analysis was performed on PubMed, Science Direct, ISI Web of Science, Cochrane, EBSCO for studies published between 1-1-2000 and 8-3-2017 comparing cognitive, affective and motivational measures in PD patients with ICD (ICD+) vs. those without ICD (ICD-). Exclusion criteria were conditions other than PD, substance and/or alcohol abuse, dementia, drug naïve patients, cognition assessed by self-report tools. Standardized mean difference (SMD) was used, and random-effect model applied. Results 10,200 studies were screened (title, abstract), 79 full-texts were assessed, and 25 were included (ICD+: 625 patients; ICD-: 938). Compared to ICD-, ICD+ showed worse performance reward-related decision-making (0.42 [0.02, 0.82], p=0.04) and set-shifting tasks (SMD=-0.49 [95% CI -0.78, -0.21], p=0.0008). ICD in PD was also related to higher self-reported rate of depression (0.35 [0.16, 0.54], p=0.0004), anxiety (0.43 [0.18, 0.68], p=0.0007), anhedonia (0.26 [0.01, 0.50], p=0.04), and impulsivity (0.79 [0.50, 1.09], p<0.00001). Heterogeneity was low to moderate, except for depression (I2=61%) and anxiety (I2=58%). Conclusions ICD in PD is associated with worse set-shifting and reward-related decision-making, and increased depression, anxiety, anhedonia and impulsivity. This is an important area for further studies as ICDs have negative impact on the quality of life of patients and their caregivers.